The Modern Concept of Homeland: Zbornik radova sa znanstvenog skupa održanog u Gospiću 26.-27. svibnja 2023., povodom 200. obljetnice rođenja Ante Starčevića (Morepress Books, 2025)
Inspired by the 200th anniversary of the birth of the Father of the Homeland, Dr Ante Starčević (May 23, 1823, Veliki Žitnik – February 28, 1896, Zagreb), the Department of Teacher Education Studies in Gospić, University of Zadar, and the State Archives in Gospić organised an international scientific conference: the 8th Šime and Ante Starčević Days, under the name The Modern Concept of Homeland (cro. Suvremeni koncept domovine), held on 26–27 May 2023 in Gospić. In a region that endowed us with the Father of the Homeland more than two centuries ago- nowadays referred to as a founder of national independence and an advocate for the right of self-determination and liberal principles in state-building, and an intriguing figure in his linguistic, political, and philosophical views – we felt it natural to explore the complex ideas of homeland and patriotism, both in a historical context and in contemporary times. In that sense, we wanted the conference to scientifically address the semantically layered notion of homeland, contextualised within the horizon of humanistic, social, and interdisciplinary perspectives. More than fifty participants from numerous Croatian and international universities attended the conference and showed significant interest in the proposed topic. The Conference Proceedings on homeland and patriotism contains 19 scholarly articles, divided into four thematic sections. The first unit includes three plenary presentations by scholars from two domestic and one international university. The first plenary presentation, held by Full Professor Pavo Barišić (University of Zagreb), under the title Lika in the Work of Ante Starčević, explores Starčević’s literary oeuvre, highlighting his connection to the Lika region. The second presentation, titled What Does Ante Starčević Mean to Us Today? The Development and (Possible) Deconstruction of a Myth, held by Full Professor Ante Bralić (University of Zadar), examines the historical and political circumstances that contributed to the mythologisation of Starčević’s figure. The third presentation, titled Manifestation of Croatian National Awareness in the Literature of Croats in Hungary, held by Dr. Stjepan Blažetin (University of Pécs), reviews the literary works of Croatian authors in Hungary and their diverse expressions of national identity. The second and third units of the Proceedings consist of papers that delve into patriotic themes from a humanistic perspective: historical, theological, and predominantly philological. They analyse the themes in a synchronic and/or diachronic context. In this sense, the papers in the chapter Patriotic Themes in Historical Context examine, from a biographical and ideological standpoint, the patriotic contributions of national leaders and less-known patriots. These papers consider the context of political and party involvement, valuing their political, pastoral, theological, and particularly patriotic efforts. The third chapter of the Proceedings, titled Philological Perspectives on Patriotic Themes, is the most extensive, encompassing twelve papers that delve into linguistic, sociolinguistic, literary-theoretical, literary-historical, and methodological investigations of the semantically complex concept of homeland. In this regard, precise analyses of Radić’s linguistic identity are presented in the light of linguistic and stylistic features of his memoir writings. The patriotic interpretations of Šime Starčević’s manuscript legacy are commendable, highlighting his refined sense of language as one of the most important markers of national identity. Following sociolinguistic research, the results of studies focusing on the language of young people are particularly intriguing, by the analyses of the ambivalent relationship between the need and the faddishness of Anglicisms versus the native language. Several manuscripts in the Proceedings address the concept of the homeland on national and international literary opus, in which, following various theoretical foundations (stylistic, imagological, narratological, etc.), attention is drawn to the characteristics of national identity; from the travelogue representation of the homeland landscape, and interpretation of patriotic ideologies in children’s literature, through turbulent premonitions of homeland(s) during wartime, to the emotional upheavals of literary characters contextualized within the horizon of a lost and/or gained homeland. Significant contributions to philological research are the methodological articles focused on the reception perspectives of patriotic themes, from primary school to higher education levels. The last but not least important section in the Proceedings includes manuscripts that, from a demographic-geographic standpoint, present interesting research results related to young people’s attitudes towards the homeland, patriotism, and national issues. The publication of the Proceedings is made possible primarily thanks to the contributions of authors from diverse Croatian universities, polytechnics, scientific, cultural, and educational institutions, as well as from abroad. We would also like to give our thanks to the reviewers of the individual papers and the reviewers of the entire Proceedings, Assistant Professor Tin Lemac, PhD, and Senior Research Associate Andrea Radošević, PhD, whose critical reading of the Proceedings and constructive suggestions have significantly contributed to its quality. We are delighted by the keen interest shown by scholars in contributing their reflections, analyses, research, and insights on the themes of homeland and patriotism as socially and historically conditioned categories. Despite the turbulence of contemporary worldviews, these contributions maintain an affirmative stance toward national values. We are pleased to present the Proceedings to the cultural community, where we hope it will find a receptive readership.